Extraction and identification of chemical and molecular compounds of Rosa damascene Mill) essence in different genotypes cultivated in some provinces of Iran - Shahbazi, Khosro; Assareh, Mohamad Hosein; Rezaee, Mohamadbagher (Cellular and Molecular Biology, 2020)
The Rosa damascena Mill. is cultivated in different parts of Iran. For evaluation of its essence, the experiment was carried out on 50 accessions during 2014-17 using randomized complete blocks design with three replications. Results showed that the essence of Kermanshah11 (0.412 g), Yazd 1 (0.400 g), Isfahan 4 (0.364 g), Lorestan 1 (0.361 g), Kermanshah 2 (0.350 g) and Isfahan 3 (0.331 g) accessions had a higher amount of essence. Strong positive correlation coefficients (pâ‰¤0.01) were found between essence of citronellol- n-eicosan (0.845), citronellol- n-heneicosane (0.879), n-nonadecane-geraniol (0.883), n-heneicosane-geraniol (0.842), n-heneicosane- geraniol (0.850), n-eicosane- geraniol (0.885), n-nonadecane- geraniol (0.930). Comparing the years, the accessions of Isfahan 5, Arak 1, Kordestan 1, West Azarbaijan 1, Tehran 1, Arak1, Fars 1 and Zanjan1 had the highest citronellol, geraniol, geraniol, n-tetradecanal, n-nonadecane, n-eicosane, n-pentacosane, n-heneicosane, respectively.